The Asian Studies Parade Archival, Biographical, Institutional and Post-Colonial Approaches - van der Velde, Paul (Leiden University Press, 2023)
The Asian Studies Parade reflects a lifetime of commitment to the field by Paul van der Velde, a leading Asian studies innovator, scholar, and publisher. The first chapters examine aspects of the Dutch colonial presence in Asia and its intellectual support system in the Netherlands. The author's engagement with historical biography emerges in studies of such contrasting figures as Japanese interpreter Imamura Gen'emon Eisei, pioneering anthropologist P.J. Veth, and anti-colonialist Jacob Haafner. Van der Velde then continues to describe the development of Asia-Europe links at the end of the 20th century and the emergence of the 'New Asia Scholar' in the 21st century. This unique work will interest anyone concerned with wider issues in Asian studies.